Intercellular Communication by Vascular Endothelial Cell-Derived Extracellular Vesicles and Their MicroRNAs in Respiratory Diseases - Fujimoto, Shota; Fujita, Yu; Kadota, Tsukasa; Araya, Jun; Kuwano, Kazuyoshi (Frontiers in Molecular Biosciences, 2021)
Respiratory diseases and their comorbidities, such as cardiovascular disease and muscle atrophy, have been increasing in the world. Extracellular vesicles (EVs), which include exosomes and microvesicles, are released from almost all cell types and play crucial roles in intercellular communication, both in the regulation of homeostasis and the pathogenesis of various diseases. Exosomes are of endosomal origin and range in size from 50 to 150 nm in diameter, while microvesicles are generated by the direct outward budding of the plasma membrane in size ranges of 100–2,000 nm in diameter. EVs can contain various proteins, metabolites, and nucleic acids, such as mRNA, non-coding RNA species, and DNA fragments. In addition, these nucleic acids in EVs can be functional in recipient cells through EV cargo. The endothelium is a distributed organ of considerable biological importance, and disrupted endothelial function is involved in the pathogenesis of respiratory diseases such as chronic obstructive pulmonary disease, pulmonary hypertension, and acute respiratory distress syndrome. Endothelial cell-derived EVs (EC-EVs) play crucial roles in both physiological and pathological conditions by traveling to distant sites through systemic circulation. This review summarizes the pathological roles of vascular microRNAs contained in EC-EVs in respiratory diseases, mainly focusing on chronic obstructive pulmonary disease, pulmonary hypertension, and acute respiratory distress syndrome. Furthermore, this review discusses the potential clinical usefulness of EC-EVs as therapeutic agents in respiratory diseases.